(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
Our research was focused on how the acquisition of a second language in pre-school students does not harm but benefits, and specifically how it helps to expand students´ vocabulary based on the fact that the more vocabulary in Spanish, the more they learn or have in English. In addition, we focused on the oral part in which we did evaluate how students know and produce correctly the vocabulary presented through flashcards. The sample consisted of a group of 40 (n = 40) 4 year - old children of a bilingual school in northern Madrid. The methodology followed showed a certain amount of flashcards based on the vocabulary they were learning in the classroom so that students could produce orally what they saw in the different images. Regarding the acquisition of vocabulary in other language than their mother tongue, there are several aspects to consider; first, we had to make reference to age. The smaller a child is exposed to a language, the faster and better he or she will learn, and second it must be said that following the results of our study, in our case, the more Spanish vocabulary our students have, the more English vocabulary they learn. Moreover, in our sample, those whose chronological age was younger had lower vocabulary both in Spanish and in English.